Multiparametric flow cytometry highlights B7-H3 as a novel diagnostic/therapeutic target in GD2neg/low neuroblastoma variants. Issue 4 (1st April 2021) - Dondero, Alessandra; Morini, Martina; Cangelosi, Davide; Mazzocco, Katia; Serra, Martina; Spaggiari, Grazia Maria; Rotta, Gianluca; Tondo, Annalisa; Locatelli, Franco; Castellano, Aurora; Scuderi, Francesca; Sementa, Angela Rita; et al.
Abstract : Background: High-risk neuroblastomas (HR-NBs) are rare, aggressive pediatric cancers characterized by resistance to therapy and relapse in more than 30% of cases, despite using an aggressive therapeutic protocol including targeting of GD2. The mechanisms responsible for therapy resistance are unclear and might include the presence of GD2neg/low NB variants and/or the expression of immune checkpoint ligands such as B7-H3. Method: Here, we describe a multiparametric flow cytometry (MFC) combining the acquisition of 10 6 nucleated singlets, Syto16pos CD45neg CD56pos cells, and the analysis of GD2 and B7-H3 surface expression. 41 bone marrow (BM) aspirates from 25 patients with NB, at the onset or relapse, are analyzed, comparing results with cytomorphological analysis (CA) and/or immunohistochemistry (IHC). Spike in experiments assesses the sensitivity of MFC. Kaplan-Meier analysis on 498 primary NBs selects novel prognostic markers possibly integrating the MFC panel. Results: No false positive are detected, and MFC shows high sensitivity (0.0005%). Optimized MFC identifies CD45negCD56pos NB cells in 11 out of 12 (91.6%) of BM indicated as infiltrated by CA, 7 of which coexpress high levels of GD2 and B7-H3. MFC detects CD45negCD56posGD2neg/low NB variants expressing high surface levels of B7-H3 in two patients with HR-NB (stage M) diagnosed at 53 and 139 months of age. One of them has a non-MYCN amplified tumor with unusual THpos PHOX2Bneg phenotype, which relapsed 141 months post-diagnosis with BM infiltration and a humerus lesion. All GD2neg/low NB variants are detected in patients at relapse. Kaplan-Meier analysis highlights an interesting dichotomous prognostic value of MML5, ULBPs, PVR, B7-H6, and CD47, ligands involved in NB recognition by the immune system. Conclusions: Our study validates a sensitive MFC analysis providing information on GD2 and B7-H3 surface expression and allowing fast, specific and sensitive evaluation of BM tumor burden. With other routinely used diagnostic and prognostic tools, MFC can improve diagnosis, prognosis, orienting novel personalized treatments in patients with GD2low/neg NB, who might benefit from innovative therapies combining B7-H3 targeting.